2001
DOI: 10.1074/jbc.m101666200
|View full text |Cite
|
Sign up to set email alerts
|

Circular Proteins in Plants

Abstract: Much interest has been generated by recent reports on the discovery of circular (i.e. head-to-tail cyclized) proteins in plants. Here

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
158
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(160 citation statements)
references
References 40 publications
(56 reference statements)
2
158
0
Order By: Relevance
“…MCoTI-II synthesised by this chemoenzymatic method was identical in all respects to naturally occurring MCoTI-II. 18,19,29,36 Interestingly, concomitant release of a small amount (8%) of rf-MCoTI-II is observed, although it was absent from the This facile new route to MCoTI-II was explored in a series of experiments that show that PST possesses ligase specificity for positively charged (Arg/Lys) residues at P 1 in the inhibitory loop. The open-chain forms of the naturally 50 occurring cyclotide MCoTI-I (P 1 =Lys) and three MCoTI-II analogues in which P 1 was changed to Arg, Gln or Phe (Table 2) were synthesised by SPPS, and subjected to the refolding and PST-mediated ligation conditions described above.…”
Section: Chemoenzymatic Synthesis Of Engineered Mcoti Cyclotidesmentioning
confidence: 99%
See 2 more Smart Citations
“…MCoTI-II synthesised by this chemoenzymatic method was identical in all respects to naturally occurring MCoTI-II. 18,19,29,36 Interestingly, concomitant release of a small amount (8%) of rf-MCoTI-II is observed, although it was absent from the This facile new route to MCoTI-II was explored in a series of experiments that show that PST possesses ligase specificity for positively charged (Arg/Lys) residues at P 1 in the inhibitory loop. The open-chain forms of the naturally 50 occurring cyclotide MCoTI-I (P 1 =Lys) and three MCoTI-II analogues in which P 1 was changed to Arg, Gln or Phe (Table 2) were synthesised by SPPS, and subjected to the refolding and PST-mediated ligation conditions described above.…”
Section: Chemoenzymatic Synthesis Of Engineered Mcoti Cyclotidesmentioning
confidence: 99%
“…23 Syntheses of several small to 35 medium size cyclotides have been reported [24][25][26][27][28] The cyclotides MCoTI-I and MCoTI-II were first isolated from the dormant seeds of Momordica cochinchinensis, and have been shown to be very potent (sub-nM) inhibitors of trypsin. 18 Whilst the MCoTI trypsin inhibitor cyclotides do 40 not share significant sequence homology with other cyclotides beyond the presence of the three cystine bridges, solution NMR has shown that they do indeed adopt a backbone-cyclic cystine-knot topology (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] The third subfamily, the trypsin inhibitor cyclotides, comprises only two members, which are present in the seeds of Momordica cochinchinensis, a tropical vine from the Cucurbitaceae plant family. Although the trypsin inhibitor cyclotides have the CCK motif, their amino acid sequences differ significantly from those of Möbius and bracelet cyclotides [15,27] but are similar to a family of linear squash trypsin inhibitors. [28] They are also referred to as cyclic knottins.…”
mentioning
confidence: 99%
“…Three-dimensional structures and sequences of selected cyclotides from each of the three subfamilies. The structures of kalata B1 (PDB ID code 1nb1), [36] cycloviolacin O1 (PDB ID code 1nbj), [36] and MCoTI-II (PDB ID code 1ib9) [27] are shown with the lowest-energy structure on top and an ensemble of the 20 lowest-energy structures below. The structures were drawn using MOLMOL.…”
mentioning
confidence: 99%